Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1177/095440700321700909
|View full text |Cite
|
Sign up to set email alerts
|

Combustion characteristics of compressed natural gas/diesel dual-fuel turbocharged compressed ignition engine

Abstract: The combustion characteristics of a turbocharged natural gas and diesel dual-fuelled compression ignition (CI) engine are investigated. With the measured cylinder pressures of the engine operated on pure diesel and dual fuel, the ignition delay, effects of pilot diesel and engine load on combustion characteristics are analysed. Emissions of HC, CO, NOx and smoke are measured and studied too. The results show that the quantity of pilot diesel has important effects on the performance and emissions of a dual-fuel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 6 publications
(6 reference statements)
0
9
0
Order By: Relevance
“…Shenghua et al [44], testing a WD 615-64 super feed diesel engine, with maximum power of 164 kW at 2,200 rpm and specific consumption of 228 g/kWh, have reported that the CO emissions of the engine operating at 1,000 rpm increased when the methane concentration (gas) was higher, reaching values of approximately 0.2 %, for a percentage of gas equal to 84 %.…”
Section: Results and Analysismentioning
confidence: 97%
“…Shenghua et al [44], testing a WD 615-64 super feed diesel engine, with maximum power of 164 kW at 2,200 rpm and specific consumption of 228 g/kWh, have reported that the CO emissions of the engine operating at 1,000 rpm increased when the methane concentration (gas) was higher, reaching values of approximately 0.2 %, for a percentage of gas equal to 84 %.…”
Section: Results and Analysismentioning
confidence: 97%
“…The size of the pilot has a very significant influence on the level of the UBHC in the exhaust gases emissions as clarified by Ref. [10]. At very lean equivalence ratios operation, the utilization of the gaseous fuel is improved significantly with an increase in the quantity of the pilot fuel due to the increased rates of combustion.…”
Section: The Effect Of Equivalence Ratiomentioning
confidence: 99%
“…Theoretical results are validated against experimental values, which were obtained at various speeds and loads from a single cylinder DI diesel engine operating under dual fuel mode at fixed pilot fuel quantity and normal injection advance without air inlet preheating (normal pilot ignited dual fuel operation -NPDFO). Moreover, model predictions are contrasted with additional experimental results obtained from the literature [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]28,29] to ensure that the two-zone model predicts with reasonable accuracy the effect of pilot fuel quantity and air inlet preheating on engine performance characteristics, soot, NO and CO emissions. This comparison revealed that the developed model captures more in a qualitative rather than in quantitative manner the influence of pilot fuel quantity and intake air preheating on engine performance and exhaust emissions.…”
Section: Introductionmentioning
confidence: 99%
“…According to prior studies [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], alterations in various engine operating parameters, such as pilot fuel quantity, pilot diesel fuel injection timing and air inlet preheating, may be used to improve the engine efficiency and to restrain the increase of CO and HC emitted from a compression ignition engine running under pilot ignited natural gas diesel operating mode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation